Block vs. Weekly Undulating Periodized Resistance Training Programs in Women. Issue 10 (October 2015) - Bartolomei, Sandro; Stout, Jeffrey R.; Fukuda, David H.; Hoffman, Jay R.; Merni, Franco
Abstract : Abstract: Bartolomei, S, Stout, JR, Fukuda, DH, Hoffman, JR, and Merni, F. Block vs. weekly undulating periodized resistance training programs in women. J Strength Cond Res 29(10): 2679–2687, 2015—The aim of this study was to compare the effects of resistance training using block periodization (BP) and weekly undulating (WUD) model on maximal strength and hypertrophy in recreationally strength trained women. Seventeen recreationally trained women were randomly assigned to either a BP group ( n = 9; age = 24.7 ± 4.2 years; body mass = 62.1 ± 5.3 kg; height = 166.4 ± 6.0 cm) or a WUD group ( n = 8; age = 23.2 ± 2.2 years; body mass = 59.8 ± 11.9 kg; height = 160.1 ± 4.1 cm). Participants of both groups trained 3 days a week for 10 weeks. The BP and WUD programs used the same exercises, and the difference between the 2 programs was in the distribution of the training volume within each training phase. Anthropometric measures and strength testing were performed before (PRE) and after 10 weeks (POST) of training. The results revealed that both BP and WUD groups made significant increases in strength and power, but improvements in lower-body strength were significantly ( p = 0.039) greater in the WUD group (+27.7%) compared with the BP group (+15.2%). Both groups significantly increased arm muscle hypertrophy ( p < 0.001), whereas improvements in thigh muscle size were significant in the WUD group only (+5.8%, p = 0.001). Results of this study indicate that the WUD model is more effective than the BP model for increasing maximal strength and muscle size in the lower body in women.